From medical devices to everyday products: exploring cross-cultural perceptions of assistive technology. Issue 2 (3rd July 2019) - Spinelli, Gabriella; Micocci, Massimo; Martin, Wendy; Wang, Yu-Han
Abstract: Currently, the assistive technologies (ATs) market is underdeveloped, which limits individual choices. Many people appear reconciled to using available products that, at best, match functionalities to compensate for physical deficiencies. Yet people express a desire for personalized, elegant, discreet and bold artefacts that match their lifestyle and provide opportunities for self-expression. This study adopts a materiality-inspired methodology to explore ATs and to elicit insights into the perceptions and emotions of the study participants towards them. A comparative exploratory study between the UK and Taiwan has been conducted to explore diverse and cross-cultural perceptions. The findings suggest that the design of ATs needs to go beyond traditional considerations, such as price and compliance, and instead focus on how these products enhance users' positive sense of self. This in return may increase the rate of successful adoption of ATs in everyday life.